Bali Mandara Hospital; Noble Purpose, Controversial results - Ida Ayu Adi Trisnawathi (Bali Tourism Board, 2017)
As a commitment to improve health services in Bali, the Bali Provincial Government built Bali Mandara International Hospital. The hospital is to be expected becoming the best hospital in Bali. aimed to help the poor family to get the best health care. can be directed to become a medical tourism destination. However, There was some commotion on the employee’s recruitment process of Bali Mandara Hospital, where violations allegedly occurred in the process of recruitment of new employees, especially in recruiting non-government contract workers. The demonstration of Sanur community also occurred on October 28th, 2017 to demand justice and transparency in the recruitment of employees at the newly built hospital where they were promised to get ten percent quota for the job vacancies. although facing many problems, the Hospital keep operating until now. The employee recruitment system that is considered not transparent, cause the noble goal of Bali Provincial Government to improve the community’s health service through Bali Mandara Hospital is not well conveyed. Corruption, Collusion and nepotism practices that are still firmly rooted in some agencies make public’s trust toward Government become low. in addition, the public is expected to be more careful in receiving information. Because if the information is misleading, it could result in the disadvantage of many parties.